Physico-chemical and spectroscopic investigation of flavonoid dispersed CnTAB micelles - Dileep Kumar; K. M. Sachin; Naveen Kumari; Ajaya Bhattarai (Royal Society Open Science, 2022)
In this study, kaempferol (0.2 m/mmol kg−1) dispersed cationic surfactant micelles were prepared as a function of alkyltrimethylammonium bromide (CnTAB) hydrophobicity (C = 12 to C = 16). The dispersion study of kaempferol in different CnTAB, i.e. dodecyltrimethylammonium bromide (C = 12), tetradecyltrimethylammonium bromide (C = 14) and hexadecyltrimethylammonium bromide (C = 16), was conducted with the physico-chemical properties of density, sound velocity, viscosity, surface tension, isentropic compressibility, acoustic impedance, surface excess concentration and area occupied per molecule and thermodynamic parameters Gibbs free energy, enthalpy and activation energy measured at 298.15 K. These properties were measured with varying concentration of CnTAB from 0.0260 to 0.0305 mol kg−1 in a 10% (w/w) aqueous dimethyl sulfoxide solvent system. The variations in these measured properties have been used to infer the kaempferol dispersion stability via hydrophobic–hydrophilic, hydrophilic–hydrophilic, van der Waals, hydrogen bonding and other non-covalent interactions.